FRI0134 Increased progression of carotid intima media thickness in thyroid peroxidase antibody positive rheumatoid arthritis patients. (23rd January 2014) - Raterman, H.; Voskuyl, A. E.; Simsek, S.; Schreurs, M.; Hoogstraten, I. V.; Peters, M.; Halm, V. V.; Dijkmans, B.; Lips, P.; Lems, W.; Nurmohamed, M.
Abstract : Background: Coexistence of autoimmune disorders was recently demonstrated for rheumatoid arthritis (RA) and hypothyroidism, and, interestingly, this coexistence amplifies the elevated cardiovascular risk in RA. Autoimmune hypothyroidism is characterised by the presence of thyroid peroxidase antibodies (TPOabs). Whether TPOabs are associated with increased CVD risk has not been studied extensively. Objectives: The aim of this study was firstly to determine the prevalence of TPOabs in RA and secondly to assess whether their presence was associated with cardiovascular disease (CVD). Moreover, this study explored whether TPOabs were related to disease specific parameters in RA patients. Methods: Data from the CARRÉ Study, an ongoing study investigating cardiovascular diseases and its risk factors in RA (n = 353) was used to ascertain the prevalence of TPOabs in RA patients. Additionally, cardiovascular and RA disease characteristics were compared between and cardiovascular and RA parameters were compared between TPOabs positive and negative patients. Results: TPOabs were present in 47/322 (15%) RA patients and TPOabs were associated with higher TSH levels (p = 0.048). CVD was observed in 22% of TPOabs positive patients compared to 17% of the TPOabs negative patients (p = 0.44). Linear regression analyses revealed a significantly larger progression of carotid Intima Media Thickness (cIMT) in TPOabs positive compared to TPOabs negative patients (p = 0.032). Disease activity scores (DAS28) were higher in TPOabs positive patients compared to TPOabs negative patients (4.4 ± 1.3 vs 3.8 ± 1.4, p = 0.018). A significant lower percentage of the TPOabs positive compared to TPOabs negative RA patients were in a low disease activity state (DAS28 < 3.2), respectively 16% and 32% (OR: 0.36, 95% CI: 014 – 0.88, p = 0.032). Conclusions: In this study the presence of TPOabs was associated with increased cIMT progression. Moreover, an association between TPOabs and RA disease activitiy was observed. Hence, TPOabs seems to have a role in the amplified CV risk in hypothyroid patients. Disclosure of Interest: None Declared